Lifetime Enhancement in Wireless Sensor Networks: A Theoretical Review - Dhull, K; Kumar, S; Ahlawat, A; Dahiya, S (International Journal of Computer Sciences and Engineering, 2025)
A Wireless Sensor network (WSN) is defined as network of devices that is used to monitor the physical conditions and gather the information from the complex geological range through wireless link. These networks are powered using batteries which are difficult to recharge. In WSN, energy can be consumed usefully or wastefully and toimprove the efficiency of WSN it is necessary to minimize the wastage of energy thereby improving the lifetime of network. Energy conservation is used to minimize the consumption of energy in several intermediate nodes to enhance the lifetime of network. This paper presents a brief overview of architecture of WSN and highlights the area where energy is consumed wastefully and usefully. Some of the techniques which are used for enhancing the network’s lifetime by reducing energy consumption are analyzed in detailed